Star-forming Nuclear Clusters in Dwarf Galaxies Mimicking Active Galactic Nucleus Signatures in the Mid-infrared - Megan R. Sturm; Bayli Hayes; Amy E. Reines (The Astrophysical Journal)
Effectively finding and identifying active galactic nuclei (AGNs) in dwarf galaxies is an important step in studying black hole formation and evolution. In this work, we examine four mid-infrared (IR)-selected AGN candidates in dwarf galaxies with stellar masses between M _⋆  ~ 10 ^8 and 10 ^9 M _⊙ and find that the galaxies are host to nuclear star clusters (NSCs) that are notably rare in how young and massive they are. We perform photometric measurements on the central star clusters in our target galaxies using Hubble Space Telescope optical and near-IR imaging and compare their observed properties to models of stellar population evolution. We find that these galaxies are host to very massive (~10 ^7 M _⊙ ), extremely young (≲8 Myr), and dusty (0.6 ≲  A _v  ≲ 1.8) NSCs. Our results indicate that these galactic nuclei have ongoing star formation, are still at least partially obscured by clouds of gas and dust, and are most likely producing the extremely red AGN-like mid-IR colors. Moreover, prior work has shown that these galaxies do not exhibit X-ray or optical AGN signatures. Therefore, we recommend caution when using mid-IR color–color diagnostics for AGN selection in dwarf galaxies, since, as directly exemplified in this sample, they can be contaminated by massive star clusters with ongoing star formation.